Epidendrum alejandrinae (Orchidaceae: Laeliinae), a new species from the high Andean forests of central Peru - Quispe-Melgar, Harold Rusbelth; Llacua-Tineo, Yashira Stefani; Ames-Martínez, Fressia Nathalie; Huayta, David; Lagones Poma, Katherine Lucero; Hágsater, Eric (Phytotaxa, 2022)
The high Andean forests harbor great and unique biodiversity. Here, we report a new species of Epidendrum from Peru. Epidendrum alejandrinae is described, illustrated and compared with the morphologically similar Epidendrum ochoae, Epidendrum pachydiscum and Epidendrum aida-alvareziae. We performed a systematic review of herbarium information on the species reported for the Region of Huancavelica and compared the morphological features of the closest species to rule out possible matches. The new species is characterized by a short, foliate aggregate stems, an apical pendulous inflorescence formed from the stem, green resupinate flowers opening in succession, the petals and sepals semi-extended, a 3-lobed lip, lateral lobes obliquely ovoid, median lobe broadly cuneate, bicallose, and four, obovoid, laterally compressed pollinia. The novelty represents an important record for the flora associated with the high Andean forest dominated by Polylepis and Gynoxys in central Peru.